Public perception of isolation, quarantine, social distancing and community containment during COVID-19 pandemic - Tahreem Hussain; Nida Jawed; Saba Mughal; Kashif Shafique (BMC, 2022)
Abstract Background Effective strategies of prevention have been and can aid in reducing and overcoming contagious diseases including COVID-19, still there is dearth of knowledge regarding general public awareness and perception. The current study aims to determine the existing knowledge and perception of people living in Karachi about isolation, quarantine, social distancing and community containment. Methods This cross-sectional online survey was conducted during the months of March and April 2020. The study included men and women of age 18 years and above quarantined during COVID-19. Convenience sampling followed by snowball sampling technique was used. An online structured questionnaire was developed using Google Form. It included questions on socio demographic information, public knowledge and perception about isolation, quarantine, social distancing and community containment. Chi-square test was used for categorical variables and p value of < 0.05 was considered statistically significant. Results A total of 548 participants were involved in this survey, 34% (n = 184) males with a mean age of 28 ± 10 years ranging from 18 to 75 years. The major source of hearing about COVID-19 was social media (72%, n = 393). Overall knowledge scores revealed that 27% (n = 146) participants had excellent knowledge about symptoms and prevention of the COVID-19. Excellent knowledge of quarantining, isolation and community containment and social distancing was 38% among participants. Participants who had good and excellent knowledge were more likely to have positive perception of isolation (p-value < 0.001). Majority participants (89%, n = 487) felt isolation may or may not be against human rights and this perception was found significantly associated with moderate to excellent knowledge about community mitigation measures (p-value = 0.009). Conclusion This study concludes that optimal public knowledge and perception related to certain aspects of isolation, quarantine, social distancing and community containment exists however knowledge gaps and misperceptions prevail that need to be addressed.